2016
DOI: 10.1177/0271678x16630322
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of tumor oxygenation and its impact on treatment response in bevacizumab-treated recurrent glioblastoma

Abstract: Antiantiogenic therapy with bevacizumab in recurrent glioblastoma is currently understood to both reduce microvascular density and to prune abnormal tumor microvessels. Microvascular pruning and the resulting vascular normalization are hypothesized to reduce tumor hypoxia and increase supply of systemic therapy to the tumor; however, the underlying pathophysiological changes and their timing after treatment initiation remain controversial. Here, we use a novel dynamic susceptibility contrast MRI-based method, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 39 publications
2
33
0
Order By: Relevance
“…In this context, it has been reported that early changes of magnetic resonance imaging (MRI) parameters can occur in glioblastoma patients who receive the anti-angiogenic multi-tyrosine kinase inhibitor cediranib, and those are in line with the normalization hypothesis (explained in the 'Introduction'), improving tumor perfusion, at least during a normalization time window, which might help radio-and chemotherapy [7,10,[34][35][36]. For bevacizumab, however, it has been suggested that tumor oxygenation might actually be worsened and not improved in patients during the phase where vascular normalization occurs, which would speak against the benefit from vascular normalization for additional cytotoxic therapy in this condition [11]. Of note, multimodal MRI patterns analyzed by novel machine learning algorithms, i.e.…”
Section: Can We Better Select Patients With Biomarkers?supporting
confidence: 52%
“…In this context, it has been reported that early changes of magnetic resonance imaging (MRI) parameters can occur in glioblastoma patients who receive the anti-angiogenic multi-tyrosine kinase inhibitor cediranib, and those are in line with the normalization hypothesis (explained in the 'Introduction'), improving tumor perfusion, at least during a normalization time window, which might help radio-and chemotherapy [7,10,[34][35][36]. For bevacizumab, however, it has been suggested that tumor oxygenation might actually be worsened and not improved in patients during the phase where vascular normalization occurs, which would speak against the benefit from vascular normalization for additional cytotoxic therapy in this condition [11]. Of note, multimodal MRI patterns analyzed by novel machine learning algorithms, i.e.…”
Section: Can We Better Select Patients With Biomarkers?supporting
confidence: 52%
“…ox.ac.uk/fsl/fslwiki/FSL) by P.K. and a neuroradiologist (D.B., with 15 years of experience in image processing) as described previously (14,16). First, brain voxels were isolated by generating a binary brain mask from the T1-weighted volume sequence by using the brain extraction tool (20) and were transferred to all other volume imaging sequences (postcontrast T1-weighted, FLAIR, diffusion-weighted imaging, ADC mapping, first temporal volume of dynamic susceptibility-weighted MR imaging raw data, relative CBV map) for each patient.…”
Section: Image Postprocessing and Radiomic Feature Extractionmentioning
confidence: 99%
“…and D.B. on the T1 subtraction volume images to select the contrastenhancing portion of the whole tumor and the nonenhancing portion (defined as FLAIR hyperintense abnormality, excluding the contrast-enhancing and necrotic tumor portion) by using a region-growing segmentation algorithm implemented with software (ITK-SNAP; www.itksnap.org [23]), as described previously (Fig 1a) (14,16).…”
Section: Image Postprocessing and Radiomic Feature Extractionmentioning
confidence: 99%
See 2 more Smart Citations